Active site plasticity and possible modes of chemical inhibition of the human DNA deaminase APOBEC3B. Issue 1 (24th December 2019) - Shi, Ke; Demir, Özlem; Carpenter, Michael A.; Banerjee, Surajit; Harki, Daniel A.; Amaro, Rommie E.; Harris, Reuben S.; Aihara, Hideki
Abstract: The single‐stranded DNA cytosine deaminase APOBEC3B (A3B) functions in innate immunity against viruses, but it is also strongly implicated in eliciting mutations in cancer genomes. Because of the critical role of A3B in promoting virus and tumor evolution, small molecule inhibitors are desirable. However, there is no reported structure for any of the APOBEC3‐family enzymes in complex with a small molecule bound in the active site, which hampers the development of small molecules targeting A3B. Here we report high‐resolution structures of an active A3B catalytic domain chimera with loop 7 residues exchanged with those from the corresponding region of APOBEC3G (A3G). The structures reveal novel open conformations lacking the catalytically essential zinc ion, with the highly conserved active site residues extensively rearranged. These inactive conformations are stabilized by 2‐pyrimidone or an iodide ion bound in the active site. Molecular dynamics simulations corroborate the remarkable plasticity of the engineered active site and identify key interactions that stabilize the native A3B active site. These data provide insights into A3B active site dynamics and suggest possible modes of its inhibition by small molecules, which would aid in rational design of selective A3B inhibitors for constraining virus and tumor evolution.